Electricity Production, Energy Consumption and Capital Formation: Analyzing the Footprints in Indonesia - Pugu, Melyana R.; Yani, Yanyan M.; Dharmawan, Wawan B.; Wanggai, Velix V.; Zakaria, Zuhaina (International Journal of Energy Economics and Policy, 2021)
We aim to investigate the effect of gross and fixed form of capital formation on electricity production and energy consumption in Indonesia during the period 1993-2018. Our found results are suggesting that most of the gross/fixed capital formation measures are not affecting either the electricity production or the energy production in Indonesia. However, more specifically key measures of gross/fixed capital formation like Gross fixed capital formation, private sector (% of GDP) and Gross fixed capital formation, private sector (current LCU) are showing their mixed impact on Electricity production from renewable sources, excluding hydroelectric (% of total), and Electricity production from renewable sources, excluding hydroelectric (kWh). On the other hand, Gross fixed capital formation (annual % growth) has its Fossil fuel energy consumption (% of total), and Renewable energy consumption (% of total final energy consumption). The stated findings have some limited implications for the financial analysts and policy makers dealing with the electricity production and overall consumption of fossil fuel and renewable energy sources. Yet, this research is confined to Indonesian economy; however, adding the other regional economies in future studies may provide some different results. Keywords: cross/fixed capital formation, energy consumption, electricity production JEL Classifications: K32, H54, D24 DOI: https://doi.org/10.32479/ijeep.10940